COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

Secretome of Adipose-Derived Stem Cells Cultured in Platelet Lysate Improves Migration and Viability of Keratinocytes - Hermann, Maike; Peddi, Ajay; Gerhards, Alexander; Schmid, Rafael; Schmitz, Deborah; Arkudas, Andreas; Weisbach, Volker Günter; Horch, Raymund E.; Kengelbach-Weigand, Annika (International Journal of Molecular Sciences, 2023)
Chronic wounds depict a silent epidemic challenging medical professionals worldwide. Regenerative medicine uses adipose-derived stem cells (ADSC) in promising new therapies. In this study, platelet lysate (PL) as a xenogen-free substitute for foetal bovine serum (FBS) in ADSC culture was used to create an ADSC secretome containing cytokines for optimal wound healing conditions. The ADSC secretome was tested on keratinocytes for migrational behaviour and viability. Therefore, human ADSC were characterized under FBS (10%) and PL (5% and 10%) substitution, regarding morphology, differentiation, viability, gene and protein expression. ADSC were then cultured in 5% PL and their secretome was used for stimulation of keratinocyte migration and viability. To enhance the effect, ADSC were treated with Epithelial Growth Factor (EGF, 100 ng/mL) and hypoxia (1% O₂). In both PL and FBS groups, ADSC expressed typical stem cell markers. PL induced a significantly higher increase in cell viability compared to FBS substitution. ADSC secretome contained various beneficial proteins which enhance the wound healing capacity of keratinocytes. This could be optimized treating ADSC with hypoxia and EGF. In conclusion, the study shows that ADSC cultivated in 5% PL can effectively support wound healing conditions and can be considered as a promising new therapy for individual treatment of chronic wound disorders.
CRIS-Team Scopus Importer:2023-03-10
Keywords: adipose-derived stem cells; cell culture; cell differentiation; molecular mechanism; personalized medicine; platelet lysate; regenerative medicine; wound healing therapy